New find of rare freshwater brown algae Pleurocladia lacustris А.Braun (Phaeophyсеае) from Dnieper Estuary of the Black Sea (Ukraine) - Tkachenko, F.P. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2021)
In article reports a new find of Pleurocladia lacustris in Ukraine. The species grew in the brackish-water Dnieper Estuary (depth 0.2 m, salinity of estuary water was 4.68‰, temperature – 23 °С, pH – 7.9) P. lacustris is a filamentous benthic species, the cells of which are not calcified here, as in freshwater conditions, but are covered with a slimy sheath. It was found in fouling of bushes of green algae Cladophora glomerata (Linnaeus) Kützing and Ulva flexuosa Wulfen, as well as blue-green (Calothrix C.Agardh ex Bornet & Flahault and Oscillatoria sp.) on a concrete slab in July 2020. The thickets of Potamogeton perfoliatus L., Ruppia maritima L., and Stuckenia pectinata (L.) Börner predominated in the coastal area of the estuary. Color illustrations of the vegetative and generative organs of P. lacustris are presented, its diagnostic macroscopic and microscopic characteristics are shown, which turned out to be somewhat larger than the data of the determinants. The ecological characteristics of the algae habitat meet the known requirements. This rare species is known in about 50 localities in Europe, North America, Australia and Africa. In many countries P. lacustris is considered an endangered species and is included in the protected red lists.